The Virtue and Evolution of Localism with Corporate Social Responsibility - Little, Stuart (2012)
This paper empirically examines the impact of historical, cultural and societal context of localism within the case study of Marks and Spencer's. The empirical analysis is informed by three central principles; discourse, institutional and stakeholder. These are integrated within an analytical framework to express the evolutionary process an ideology, such as localism exists as a phenomenon, is constructed through language and then institutionalised to be taken-for-granted truth within everyday life. These steps identified show the evolution of the process from different periods of time creating new constructs of localism. This is due to changing market, cultural and political conditions that are essentially repositories of meaning for localism. Discourse analysis was used to investigate the media and corporate material communicated localism to the public and how this has changed over time. The findings suggest not only different portrayals of the concept by stakeholder groups, but also new meanings of the term have occurred by trends, issues and events that have caused institutional change. It concludes with implications that corporate involvement has on the construct with a process of ‘amoralisation’ weakening the moral connotations of the term for profit.